Spindle Cell Lipoma of the Soft Palate - Ahmet Hançer; Can Özbay; Serap Karaarslan; Muzaffer Balaban (Case Reports in Otolaryngology, 2015)
Intraoral spindle cell lipomas (SCL) are very rare and comprise ranging between 1.4%–9.8% of all intraoral lipomas. To our knowledge, no case of a SCL located on the soft palate has been reported in the English-language literature. A 31-year-old female was admitted with a swelling in her soft palate. On examination, a 3 cm sessile, nontender swelling was observed on her soft palate. After surgical excision, it was diagnosed as a SCL.